2016
DOI: 10.1016/j.drugalcdep.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of ‘Sure’: A Patient Reported Outcome Measure (Prom) for Recovery From Drug and Alcohol Dependence

Abstract: Highlights‘SURE’ is a new patient reported outcome measure of recovery from drug and alcohol dependence.‘SURE’ has been developed with significant input from people in recovery.‘SURE’ has good face and content validity, acceptability and usability for people in recovery.SURE’ comprises 21 items (5 factors) and is psychometrically valid, quick and easy-to-complete.‘SURE’ can be used by individuals in private or in a therapeutic context

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 29 publications
5
96
0
1
Order By: Relevance
“…Failure to involve patients in the process of outcome measurement raises the possibility that measurement overlooks aspects of relevance for patients and over-optimistic reporting of outcomes (Thurgood et al, 2014). Increasingly, studies are seeking the views of patients about outcome measurement criteria (e.g., Ruefli and Rogers, 2004;Neale et al, 2016;see Table 1). For instance, Ruefli and Rogers (2004) revealed that patients in treatment stated the importance of domains covering: 'making money', 'getting something good to eat', 'being housed', 'relating to family', 'getting needed programs/benefits/services', 'handling health problems', 'handling negative emotions', 'handling legal problems', 'improving oneself' and 'handling drug-use problems'.…”
Section: Does Outcome Measurement Reflect the Concerns Of Patients?mentioning
confidence: 99%
See 3 more Smart Citations
“…Failure to involve patients in the process of outcome measurement raises the possibility that measurement overlooks aspects of relevance for patients and over-optimistic reporting of outcomes (Thurgood et al, 2014). Increasingly, studies are seeking the views of patients about outcome measurement criteria (e.g., Ruefli and Rogers, 2004;Neale et al, 2016;see Table 1). For instance, Ruefli and Rogers (2004) revealed that patients in treatment stated the importance of domains covering: 'making money', 'getting something good to eat', 'being housed', 'relating to family', 'getting needed programs/benefits/services', 'handling health problems', 'handling negative emotions', 'handling legal problems', 'improving oneself' and 'handling drug-use problems'.…”
Section: Does Outcome Measurement Reflect the Concerns Of Patients?mentioning
confidence: 99%
“…Patients reported that treatment recovery should include improvements in 'substance use', 'material resources', 'outlook on life', 'self-care' and 'relationships'. Another example is the recently developed 'SURE', a standardised outcome measure for treatment of substance use disorders (Neale et al, 2016). In this measure, items were generated in collaboration with former and current drug and alcohol service users (Neale et al, 2016).…”
Section: Does Outcome Measurement Reflect the Concerns Of Patients?mentioning
confidence: 99%
See 2 more Smart Citations
“…However, these measure HRQOL and not QOL: the Health-Related Quality of Life for Drug Abusers test (HRQoLDA [26]), the Chinese instrument Quality of Life Scale for Patients with Drug Addiction (QOL-DA [27]), and the Patient Reported Outcome Measure for Recovery from Drug and Alcohol Dependence (SURE [28]). No opioid-dependence-specific or addiction-specific QOL instrument is available to date.…”
Section: Introductionmentioning
confidence: 99%